Percepciones sobre la importancia del idioma kichwa en los estudiantes de básica superior de la “unidad educativa bilingüe Ñucanchik Yachay. - Gauin Morocho, Betty Johanna (2024)
The research focused on examining the perceptions of students at the Ñucanchik Yachay Bilingual Educational Unit regarding the importance of the Kichwa language. To achieve this objective, a qualitative methodology was adopted, employing a non-experimental research design, which implies that no manipulations or interventions were carried out; rather, information was gathered in a naturalistic manner to comprehend the perceptions of both students and teachers regarding the language. The study population comprised 42 participants, students ranging from 8th to 10th grade in upper basic education. This population was selected due to their direct role in the educational process and their connection with the Kichwa language. Data were collected through questionnaires, utilized both to obtain objective and quantitative information and to explore student perceptions in this research. The results obtained outline that students possess a strong cultural connection and value Kichwa as part of their identity, largely driven by their indigenous ethnic identity, thus supporting the implementation of didactic resources for Kichwa learning. This underscores the need for the development of strategies that strengthen advanced language skills and promote comprehensive learning.